Senior Age in Greek Media: Digital Transformation and Society - Apal'kova Tat'yana (Виртуальная коммуникация и социальные сети)
The paper deals with the media image of senior age citizens as a demographic stratum in linguistic, social, cultural, and axiological aspects. The material involved online Greek media texts on the topic of digitalization with clusters of linguistic tools that explicate the image of sixty-plusers. The research methods consisted of content analysis, description, structural and semantic analysis, and comparison, categorization, and classification. They made it possible to reveal the way elderly people behave in digital environment and the linguistic means that describe these behavior patterns. The cluster of Greek lexical units attributing this age group highlighted the current axiological profile of senior citizens in the Greek linguistic worldview, as well as some verbal markers that reflect the attitude of younger content makers and users. The modern media texts actualizing the concept of sixty-somethings demonstrated non-stereotypical perceptions and a broader semantic volume, which indicates the ongoing reformatting of social values. As a global social trend, the digital transformation of society is changing the public attitude to senior citizens: in just a decade, the new senior generation will be digitally literate. The media coverage of the way today’s senior citizens adapt to the digital environment, with all its stages and linguistic means, allows for a temporal juncture of the contemporary Greek social values.